Going local in downtown Kingston, Jamaica: Doing political ethnography and qualitative research in a volatile urban environment. (14th November 2016) - Hossein, Caroline Shenaz
Abstract : Purpose: Academics examining the global South who engage in informal politics to understand social and political issues should be prepared to diversify their methods toolkit. Informal ties and politics are where one learns about social and economic exclusion. The paper aims to discuss these issues. Design/methodology/approach: Mixed qualitative methods – such as individual interviews, surveys, and focus groups – provide an understanding of the people's perspective, enabling the researcher to truly know what is going on. Findings: Fieldwork in the downtown communities of Kingston, Jamaica, has an element of danger because violence and politics are very much a part of the daily reality of the people being interviewed. In this paper, the author argues that studying how financial resources are allocated to low-income people and understanding why some groups purposefully self-exclude themselves from economic development programs require unorthodox field methods. The author thus uses political ethnography to understand the experience of marginalized Jamaican people. Originality/value: Mixed qualitative methods and political ethnography assisted the author to understand the actual experience of marginalized people and politicized financial programs.